Potential of bone marrow mesenchymal stem cells in management of Alzheimer's disease in female rats. (17th July 2014) - Salem, Ahmed M.; Ahmed, Hanaa H.; Atta, Hazem M.; Ghazy, Mohamed A.; Aglan, Hadeer A.
Abstract Alzheimer's disease (AD) has been called the disease of the century with significant clinical and socioeconomic impacts. Pharmacological treatment has limited efficacy and only provides symptomatic relief without long‐term cure. Accordingly, there is an urgent need to develop novel and effective medications for AD. Stem cell‐based therapy is a promising approach to handling neurodegenerative diseases. Therefore, the current study aimed to explore the possible therapeutic role of single intravenous injection of bone marrow derived mesenchymal stem cells (BM‐MSCs) after 4 months in management of AD in the experimental model. The work also extended to compare the therapeutic potential of BM‐MSCs with 2 conventional therapies of AD; rivastigmine and cerebrolysin administered daily. BM‐MSCs were able to home at the injured brains and produced significant increases in the number of positive cells for choline acetyltransferase (ChAT) and survivin expression, as well as selective AD indicator‐1 (seladin‐1) and nestin gene expression. Histopathological examination indicated that BM‐MSCs could remove beta‐amyloid plaques from hippocampus. Significant improvement in these biomarkers was similar to or better sometimes than the reference drugs, clearly showing the potential therapeutic role of BM‐MSCs against AD through their anti‐apoptotic, neurogenic and immunomodulatory properties.